2022
DOI: 10.1111/ejn.15610
|View full text |Cite
|
Sign up to set email alerts
|

Main olfactory bulb reconfiguration by prolonged passive olfactory experience correlates with increased brain‐derived neurotrophic factor and improved innate olfaction

Abstract: The main olfactory bulb (MOB) is highly plastic and constantly reconfiguring its function and structure depending on sensory experience. Despite the extensive evidence of anatomical, functional and behavioural changes in the olfactory system induced by highly variable olfactory experiences, it is still unknown whether prolonged passive odour experience could reconfigure the MOB at its input and network activity levels and whether these changes impact innate olfaction. Here, by measuring odour-induced glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(182 reference statements)
0
0
0
Order By: Relevance
“…Similar results were subsequently confirmed in mice [131,137,165]. In another noteworthy recent study, one of the rare cases of true olfactory environmental enrichment, adult mice were exposed to 21 different natural or synthetic odorant blends in two one-hour sessions per day using a different odorant each day for 21 days [135]. Enriched mice were compared to non-enriched controls using habituation/dishabituation tests and a predator odor avoidance test.…”
Section: Behaviorsupporting
confidence: 54%
See 2 more Smart Citations
“…Similar results were subsequently confirmed in mice [131,137,165]. In another noteworthy recent study, one of the rare cases of true olfactory environmental enrichment, adult mice were exposed to 21 different natural or synthetic odorant blends in two one-hour sessions per day using a different odorant each day for 21 days [135]. Enriched mice were compared to non-enriched controls using habituation/dishabituation tests and a predator odor avoidance test.…”
Section: Behaviorsupporting
confidence: 54%
“…Most of these results were qualitatively similar in the awake mice, if quantitatively less robust, such that some statistical differences were not significant. In addition, local field potential recordings showed that enrichment led to an increase in slow wave network activity (<12 Hz) and a decrease in fast oscillations (>12 Hz) compared to unenriched controls, though the significance of this result is unclear [135].…”
Section: Olfactory Bulbmentioning
confidence: 99%
See 1 more Smart Citation
“…Body temperature was preserved at 37˚C using a warm water circulation system. The animal's respiration was continuously monitored with a piezoelectric sensor (40-60 breaths/minute; [45][46][47][48]). Anesthesia was stopped at the end of the session and animals were observed until complete recovery before being transported back to their place of accommodation to later be processed for histochemical studies [2,[46][47][48][49].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%